Personality traits and adherence on COVID-19 preventive measures in a two-year follow-up study - Lorenzo Casagrande Reggiani; Igor Londero; Neusa Sica da Rocha (Scientific Reports)
Abstract Preventive measures (PM) to avoid disease spread are essential, and personality traits might influence their adherence. To evaluate the impact of personality traits Psychoticism (P), Extraversion (E), and Neuroticism (N) on adherence to COVID-19 PM over time, the mediation of depressive, anxious symptoms and Lie subscale, the moderation of gender and the adjustment of age. A two-year prospective study with 619 participants. We used Eysenck Personality Questionnaire (EPQR-A) for personality and some questions to assess the adherence to PM. We used Structural Equation Modeling (SEM) with the Partial Least Squares (PLS). P had significant negative impact on adherence to all PM (β= − 0.153– (–0.125), CI95% − 0.234–0.043, p < 0.05), except Wearing masks and Working remotely. E had a minor positive impact on Desire to protect yourself and others (β = 0.095–0.144, CI95% − 0.027–0.167, p < 0.05). N had no effect on PM. Female gender showed a small moderation (β= − 0.157–(–0.095), CI95% − 0.258–0.001), p < 0.05). Lie subscale, depressive and anxious symptoms did not present a significant mediation. High P score had a negative impact on adherence to PM, especially in women. This emphasizes the need for personalized approaches in public health and clinical practice.